A Lived Catholicity: The Ecclesiologies of Pope Frances and Robert J. Schreiter, C.PP.S. - Kirch, Jeffrey S. (Interreligious Studies and Intercultural Theology, 2019)
Both Pope Francis and Robert Schreiter recognize that the world has been profoundly affected by conflict, globalization, and the breakdown of relationships on multiple levels. They also assert that the Church must address these situations. The ecclesiologies of both Schreiter and Francis offer effective tools for this work. This article will examine several key, shared concepts within their ecclesiologies. Specifically, their understandings of the missionary nature of the Church and their robust understanding of catholicity prove to be key concepts in the Church's response to a world marred by sin.